2020
DOI: 10.1177/0145561320980179
|View full text |Cite
|
Sign up to set email alerts
|

First Bite Syndrome After Parotidectomy: A Case Series and Review of Literature

Abstract: Introduction: First bite syndrome (FBS) is a rare but potentially debilitating complication observed after surgery involving the upper cervical region. Patients classically complain of severe facial pain in the ipsilateral parotid region with the first few bites of a meal. Objective: The aim of this study is to shed light on the incidence and potential risk factors of FBS, including a series of cases depicting FBS observed after parotidectomy. Methods: Retrospective review of 419 patients who underwent parotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…This systematic review examines the potential of BTA to treat FBS resulting as a surgical complication. As previously discussed, while some patients develop resolution of symptoms within 1-18 months (5,10,(19)(20)(21)(22)(23)27,52,53), up to 88% of patients continue to experience symptoms (2,5,19,24,(53)(54)(55). Botulinum toxin has had multiple applications in otolaryngology, including dystonia of the larynx (56), laryngeal granulomas (57), laryngeal joint dislocation (58), cricopharyngeal spasm (57), posterior glottic synechiae (59), blepharospasm (60), hemifacial spasm (60), temporomandibular joint disorders (61), and oromandibular dystonia (60).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This systematic review examines the potential of BTA to treat FBS resulting as a surgical complication. As previously discussed, while some patients develop resolution of symptoms within 1-18 months (5,10,(19)(20)(21)(22)(23)27,52,53), up to 88% of patients continue to experience symptoms (2,5,19,24,(53)(54)(55). Botulinum toxin has had multiple applications in otolaryngology, including dystonia of the larynx (56), laryngeal granulomas (57), laryngeal joint dislocation (58), cricopharyngeal spasm (57), posterior glottic synechiae (59), blepharospasm (60), hemifacial spasm (60), temporomandibular joint disorders (61), and oromandibular dystonia (60).…”
Section: Discussionmentioning
confidence: 79%
“…While FBS may spontaneously resolve in 6-20% of patients (2,5,19,20) and partially improve in 69-82% of patients (2,5,20); 15-18% of patients may develop undiminished, chronic pain (5,19). The time to spontaneous resolution has been reported to be from 1-18 months (10,(20)(21)(22)(23)(24). Prior medical treatments aimed at FBS include carbamazepine with and without concomitant amitriptyline (19)(20)(21)25,26), nonsteroidal anti-inflammatory drugs (20,27), opioids (28), hyoscine (28), gabapentin (19,21), pregabalin (19,29), and local anesthetics (16,19,21,28).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the results of a study showed that the incidence of FBS after parotidectomy was 2% (eight out of 419) during a follow‐up time of 16.5 months. Six out of these eight underwent partial parotidectomy by dissection of the deep lobe of the parotid 15 . In another study, a rare case of IFBS presented with severe pain and swelling in the parotid region during initial food bites in the absence of prior surgeries or tumors.…”
Section: Discussionmentioning
confidence: 97%
“…It is typically characterized by the first bite of each meal experiencing sharp pain in the ipilateral parotid gland region, which in severe cases may affect an individual’s ability to tolerate oral eating. According to the results of Xu et al ( 11 ), the incidence of FBS is about 2%. Frey syndrome, also known as auriculotemporal syndrome, refers to symptoms such as transient sweating, flushing, and abnormal sensation of the ipsilateral temporal and anterior ear skin when eating after parotid tumor surgery.…”
Section: Introductionmentioning
confidence: 97%